A Poetics of Sensibility in Giedrė Kazlauskaitė’s Poetry (Studies in Contemporary Lithuanian Poetry) - Rėklaitytė, Akvilė (Semiotika, 2025)
This article, taking the postmodernist aesthetics of the late twentieth century as a point of departure, discusses the transformed language of contemporary poetry, in which ethical sensibility and renewed lyrical intonations become increasingly prominent. Drawing on the principles of close reading and discourse analysis, the poems in Giedrė Kazlauskaitė’s collection Marialė are examined on two levels: thematically, with attention to the political and social engagement of the lyrical “I,” as revealed through new interpretations of traditional concepts such as homeland, family, and religion; and rhetorically, through an analysis of the irony characteristic of Kazlauskaitė’s poetry and its lyricism as a direct expression of feelings. The ethical sensibility of the speaking subject, manifested both in thematic concerns and in modes of expression, is associated with one of the tendencies of metamodernism – a value-oriented ethical and emotional perception of the world as a counterbalance to the to the overstimulation of contemporary life.
Keywords: metamodernism; sensibility; new sincerity; post-irony; Giedrė Kazlauskaitė; contemporary poetry; lyric poetry